(untitled) (Journal of Bio-Science, 2021)
Under this study a total of nine treatments were considered for soil amendments where organic manures, chemical fertilizer and probiotics were used to evaluate the efficiency on growth and yield of wheat. On the basis of seedling disease incidence and chlorophyll presence parameters data were recorded on seedling infection at 14 days, seedling blight at 21 days, and chlorophyll content at 70 days after sowing. In this study the same experiments were conducted up to three years (2016-2019) and data were compiled and analyzed. It was observed that the disease prevalence attributes significantly decreased in T5 (Trichoderma harzianum + vermicompost + green manuring) than other treatment combinations and control (T0). Noteworthy results were found on seedling health, application of probiotic and organic manures which significantly influenced the less infection of wheat. Besides this, chlorophyll content of wheat leaf and plant number with effective tiller enhanced largely under T8 (chemical fertilizer) than T4 (poultry manure + vermicompost + green manuring) and control (T0). The main advantage of this research is to evaluate efficiency for growing healthy wheat plant which reflects on plant growth and yield and ultimately helps for food security. J. Bio-Sci. 29(2): 61-70, 2021 (December)